The complete chloroplast genome of Lantana camara L. (Verbenaceae) - Samaila S. Yaradua; Muzammil Shah (Mitochondrial DNA. Part B. Resources, 2020)
In this study, we sequenced, assembled and reported the complete chloroplast genome of Lantana camara an important medicinal plant for the first time. The genome is circular and quadripartite in structure; it has a length of 154,388 bp, 39.2% GC content and harbored 137 genes including 90 protein-coding genes, 39 tRNAs, and 8 rRNAs. The genome contained a large single-copy of 85,198 bp and a small single-copy of 17,249 bp separated by a pair of inverted repeat regions. The phylogenetic relationship showed a close relationship between L. camara and Lippia origanoides. The plastome sequence reported in this study will help for future research on the species and evolutionary studies of Verbenaceae.